KONSEP PENDIDIKAN TASAWUF PADA REMAJA MILENIAL - Amar Habibi; Suklani (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Tasawuf education serves to make humans have pious personalities, good and noble behavior, and the best worship, producing the output in the form of honest, istiqāmah and tawadu humans. Tasawuf education for teenagers is really needed to prevent juvenile delinquency. This article aimed to identify and understand the concept of tasawuf education in order to prevent juvenile delinquency. This article used a literature review approach. The literature search was conducted online through Google Scholar which was limited from 2012-2022 with the search process using the keywords of "Tasawuf Education", "Tasawuf Education for Teenagers", and "Millennial Tasawuf Education". The result of this study shows that in general, tasawuf education is a means for a person to get closer to Allah through the purification of the soul and heart. This is what is needed to face the modern life experienced by humans, especially the millennial teens who are keen to the world of technology and the internet. Tasawuf education must also be included and presented with the latest approaches so that it relates to millennial teens. It is for the sake of creating teenagers who have good morals and protecting their personalities from spiritual crisis.